Farmer’s Motivation Towards Agroforestry-Based Agriculture to Utilize Understorey-Cropping System in BKPH Purworejo KPH Kedu Selatan - Fitri Lusiana Kurniasari; Alia Bihrajihant Raya; Roso Witjaksono (Agro Ekonomi, 2019)
Agroforestry is a land management technique to be used together with the society in the cultivation of forestry and agricultural commodities. The concept of agroforestry carried out in BKPH of Purworejo, KPH Kedu Selatan, both high economic agroforestry crops, such as rubber, coffee, cocoa, teak, mahogany, etc.; low economic agroforestry plants, such as dadap, lamtoro, kaliandra, etc.; and seasonal agroforestry plants, such as rice, corn, peanuts, and others. The land management is an important effort to improve the quality and quantity of agricultural production, which included in extensification efforts. This research aims to determine farmers' motivation in cultivating agroforestry-based agricultural commodities, to determine factors that influence motivation in cultivating agroforestry-based agricultural commodities, and to determine the effect of motivation in cultivating agroforestry-based agricultural commodities on utilizing the understorey-cropping system at BKPH Purworejo. The method used in this research was descriptive quantitative analysis method. While the data processing method used was the proportion test and regression test. The results of this research indicated that approximately less than or equal to 50% of farmers have the low motivation of farmers to cultivate agroforestry-based agricultural commodities. Factors that have a positive effect on the motivation in cultivating agroforestry-based agricultural commodities included the role of agriculture-forestry extension agents and access to the marketing of agroforestry products. While the factor that has a negative effect on the farmer’s motivation is the obligation of farmers to cooperate with Perhutani. The motivation of farmers in cultivating agroforestry-based agricultural commodities has a positive effect on utilizing the understorey-cropping system at BKPH Purworejo, KPH Kedu Selatan.